Dealing with Routing Hole Problem in Multi-hop Hierarchical Routing Protocol in Wireless Sensor Network - Sama, Najm Us (Universiti Malaysia Sarawak (UNIMAS), 2019)
A Wireless Sensor Network (WSN) consists of spatially distributed autonomous sensors which produces a measurable response to a change in a physical or chemical condition, e.g. temperature and ground composition. Most common applications of WSN are Industrial control, security and military sensing, asset tracking and supply chain management, environmental, health, traffic and building structures monitoring. Due to the battery powered sensor nodes, it is a critical requirement to manage and save the energy of WSN. Routing protocols for WSN are responsible for maintaining the routes between the source node and base station. The challenging issue of routing protocols is to reduce the communication overhead for data transmission by determining an optimal path. The hierarchical routing technique is one of the energy efficient routing protocols in WSN. In multi hop communication, the Cluster Head (CH) has to send the aggregated data to one hop away neighbor cluster head either it is far away or near to the sink, while in a single hop it makes a difference. Due to many-to-one data routing pattern, lack of energy consumption management will results early loss of CH’s energy in sink vicinity, which leads to a routing hole problem. In the proposed work, the focused problem is how to reduce the communication energy consumption and to avoid the routing hole problem by optimized routing algorithms. First, a routing hole detection algorithm is proposed prior to designing the routing protocol which decreases about 30 percent energy consumption rate, detection time and detection overhead. Second, to reduce the routing hole problem an Energy efficient Least Edge Computation (ELEC) multi-hop clustering algorithm for WSN is proposed, which achieves nearly double network lifetime by equal energy consumption in various parts of the network as compared to existing routing strategies. Further evolution of the ELEC routing protocol is presented to evaluate the impact of incremental cluster iv heads on the performance of WSN. Third, the LEACH routing protocol is modified by combining ELEC routing protocol with it. Results shows that the ELEC-LEACH routing protocol almost doubles the network lifetime, in addition just nine percent of total energy left unutilized.